PERSEPSI STAKEHOLDER DAN PRODUSEN UMKM TENTANG REBRANDING: STUDI KASUS PENCIPTAAN LOGO “DOLLY SAIKI POINT” - Jefri Setyawan; Hedi Amelia Bella Cintya; Joshi Maharani Wibowo; Hazrul Iswadi (LPPM Universitas Bina Bangsa, 2023)
The most extensive localization in Southeast Asia, Gang Dolly, has been closed by the Surabaya city government. In 2017 the Surabaya City Government launched DS (Dolly Saiki) Point as a centre for MSME products in the Dolly area to restore the community's economic sector. It has been five years running; there are still obstacles to maximizing the existing potential. These obstacles are the difficulty for the centre to be known by the public, the low frequency of people accessing DS Point and the unfamiliarity of DS Point as a souvenir centre in the City of Surabaya. The transformation of Gang Dolly that has taken place since the closure of the localization still requires branding for MSME players who grow there. One form of branding creation that can be done at Gang Dolly is to improve the promotional elements at the DS Point centre, namely the logo. This service involves relevant policymakers at the Surabaya City level, educational institutions, and SME actors. This service method uses focus group discussions, interviews, and observations. The results of the DS Point rebranding process are explained through four themes, namely: 1) Obstacles between stakeholders in MSME branding; 2) Logo as the entrance to product introduction; 3) History of the area as a forming logo element; and 4) colour psychology as a logo appeal. The service program produces outcomes and recommendations, which are reviewed in this article's results and discussion sections.